Proyecto de factibilidad para la implementación de un restaurante de comida típica de la Amazonía en la ciudad de Loja - Pardo Torres, Karla Del Cisne (2019)
The research called: "PROJECT OF FEASIBILITY FOR THE IMPLEMENTATION OF A TYPICAL FOOD RESTAURANT OF THE AMAZON IN THE CITY OF LOJA", was developed in the city of Loja, in order to determine the feasibility for the implementation of a restaurant typical food of the Amazon in the city of Loja, the same that is based on four studies: market study, technical study, administrative legal study and economic and financial study. n the research, different methods, techniques and instruments were used, such as: direct observation and the survey; the same ones that allowed to gather relevant information for the development of the project. It was surveyed 385 people aged 20 to 64 from the different urban parishes of the city of Loja and with the data published and projected to 2018, by the National Institute of Statistics and Census INEC, it was recognized that the city of Loja has 119,850 inhabitants (market segment for the present study). Likewise, the ten representatives of the main restaurants of typical food were surveyed to know their sales volume of the last years and five suppliers, who supply raw material for the production of the typical dishes of the Amazon. The market study allowed the analysis of demand and supply, obtaining an unmet demand of 247,125 people, with these data proceeded to make the marketing plan where the product strategies were determined, price, place and advertising and promotion. The technical study indicates that the restaurant will be able to serve 29,952 people per year; In addition, the location (macro and micro) was established, determining that the restaurant will be located in the Parroquia El Valle, Av. Orillas del Zamora. In what corresponds to the administrative legal study was determined the organizational design, the legal organizational, which determined the restaurant as a limited liability company, administrative levels, organizational structure and function manuals. In the financial study it was determined that the project reaches an investment of $ 30,518.00 dollars and will be financed with a contribution from the partners of 67.23% of the total investment corresponding to $ 20,518.00 and a BanEcuador loan that will constitute the 35.77% corresponding to $ 10,000 dollars at 3 years term with an annual interest rate of 11.26%. Finally, the financial evaluation was carried out with which the following results were obtained: the NPV of the research project gives a positive value of $ 70,081.77, which indicates 5 that the project is feasible, the IRR which is 75.14%, the recovery time of the investment would be 1 years, 5 months and 8 days, the cost benefit ratio is $ 1.40; the sensitivity analysis with an increase of 26.25% in costs and a decrease of 18.25% in revenues, this determines the feasibility and profitability of the project. Finally, it is concluded that this new business idea is profitable and feasible, since this is demonstrated by the four studies that have been conducted and frame this project.